2009
DOI: 10.3136/fstr.15.65
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Quality of Culinary Pork Meat in Relation to Slaughter and Technological Value

Abstract: The aim was to estimate sensory pork quality in relations to its carcass and technological value. The research was executed on 57 hogs. The studied meat from hogs were characterized by appropriate slaughter and technological value (pH, drip loss, cooking and technological yield). The large variability of visual quality of meat (colour, marbling) was observed. The appropriate visual quality of meat in relationship to marbling was originated from carcass by meatiness above 56.7%. These meat samples were also cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Another limitation of the study by Jaworska et al. (2009) is the small number of well‐trained participants, which further lowers the external validity, that is, in terms of consumer acceptance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another limitation of the study by Jaworska et al. (2009) is the small number of well‐trained participants, which further lowers the external validity, that is, in terms of consumer acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…The color of pork is usually referred to as pink or red and described in light or dark hues (e.g., Jaworska et al., 2009; Ngapo et al., 2007; Norman et al., 2003). Of the 11 articles included in this review (Table 1), two of them describe the visual assessment of raw meat samples (i.e., Jaworska et al., 2009; Norman et al., 2003), whereas the rest used photographs of raw pork chops.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result was probably associated with significantly higher levels of marbling in comparison with meat coming from P76 line. Numerous studies have confirmed a significant and positive impact of the increased marbling on sensory attributes such as tenderness, juiciness and flavour [11,13,19,20]. Fig.…”
Section: Breedmentioning
confidence: 99%